KULIAH KERJA NYATA TEMATIK MAHASISWA FAKULTAS TEKNIK UISU DI KECAMATAN AIR PUTIH KBUPTEN BATU BARA - Luthfi Parinduri; Mhd. Zulfansyuri Siambaton; Muksin R. Harahap (Jurnal Pengabdian Mitra Masyarakat, 2023)
KKNT is an academic activity of higher education which is manifested through the Tri Dharma of Higher Education, namely education and teaching, research, and community service. As in the previous year, for 2023 the UISU Faculty of Engineering dispatched 159 semester VII students to carry out KKNT activities in 13 villages (out of 19 villages/wards) in Kecamatan Air Putih, Kabupaten Batu Bara. This activity lasted for 29 days from July 26 2023 to August 23 2023. The 2023 USU Faculty of Engineering KKNT carries the theme "Utilization of Sustainable Technological Innovation in Building Civilized Villages". Based on the monitoring and evaluation carried out by the KKNT Organizing Team and UISU Faculty of Engineering Leaders, the implementation of the KKNT for 29 days in 13 villages in Kecamatan Air Putih, was generally carried out well and according to plan. This was also confirmed from the remarks of the Camat  Air Putih during the pick-up event for KKNT participants which was held on Tuesday 22 August 2023. The sub-district head said that the presence of students based on information and confirmation from the head and village officials during the implementation of the KKNT was very positive. The presence of students has contributed and added value to the community, business activities (UMKM) and officials in each village. During the implementation of this KKNT, 13 main activities have been made as community service activities, which will be further developed and used for various student activities.